2020
DOI: 10.1016/j.chest.2020.05.515
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Outcomes of 421 Patients With Coronavirus Disease 2019 Treated in a Mobile Cabin Hospital

Abstract: BACKGROUND: In December 2019, a novel coronavirus-associated pneumonia, now known as coronavirus disease 2019 (COVID-19), was first detected in Wuhan, China. To prevent the rapid spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and treat patients with mild symptoms, sports stadiums and convention centers were reconstructed into mobile hospitals. RESEARCH QUESTION: It is unknown whether a mobile cabin hospital can provide a safe treatment site for patients with mild COVID-19 symptoms. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Initial database search identified 6196 studies and 34 additional records through reference and citation searches (Figure 1). Overall, 329 of them with full‐text were reviewed for eligibility, of which 124 studies were included in this analysis 7‐9,14‐134 . The NOS scores ranged between 5 and 8.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 8,170 patients in the 35 studies included in this meta-analysis, 2,415 patients (29.56%) met the criteria for severe COVID-19. Ten studies did not report the prevalence of CHD [ 9 , 18 , 19 , 22 , 24 , 27 , 31 , 32 , 35 , 37 ], five studies did not report the prevalence of hypertension [ 14 , 20 , 32 , 36 , 39 ] and three studies did not report the prevalence of diabetes [ 24 , 34 , 36 ]. The remaining studies reported the prevalence of CHD, hypertension and diabetes in their respective patient pools.…”
Section: Resultsmentioning
confidence: 99%